Aberration-insensitive twisted wavefront detection using polarization correlation - Parvin R.; Sarkar T.; Kumar Singh R.; Brundavanam M.M. (My University, 2025)
We have demonstrated using higher-order Stokes correlations that the retrieved amplitude and phase information of the optical vortex (OV) beam and its orbital angular momentum spectrum when it is propagating through a scattering medium are insensitive to the external aberration from the optical system. A theoretical framework of the proposed technique is described and validated by considering an aberration in the propagation channel by optical system. The usefulness of the technique is demonstrated in the recovery of amplitude and phase information of an OV beam even in presence of aberration. Comparisons between aberrated and non-aberrated cases are discussed to examine and evaluate the performance of the technique. © 2022 IOP Publishing Ltd.